Evaluation of groundwater quality in Jampali coal mine, Raigarh, Chhattisgarh, India - Ahmed S.I.; Sonkar A.K.; Kishore N.; Jhariya D. (My University, 2025)
Groundwater is the main source of water for drinking, industrial, and irrigation uses for most nations. Groundwater quality deterioration occurs due to urban, agricultural, mining, and industrial expansions. This research deals with the assessment of groundwater quality index, correlation, clustering analysis, and major ions chemistry around Jampali opencast coal mine of Raigarh district, Chhattisgarh, India, where groundwater is the main source of drinking water. A total of 28 groundwater samples were collected from the different stations in the month of April 2019 and 11 physicochemical parameters were examined. The results of the physicochemical analysis showed that cation abundance follows the order Na+> K+> Mg2+> Ca2+ in the groundwater, while anion abundance follows the order Cl− > NO3− > SO42− > F−. A strong positive correlation is observed between TDS–EC, TDS–Mg2+, TDS–Na+, TDS–Cl−, TDS–SO42− (r = 0.999, 0.871, 0.872, 0.846, and 0.801) and EC–Mg2+, EC–Na+, EC–Cl−, EC–SO42− (r = 0.871, 0.873, 0.846, 0.802). The two clusters demonstrate a blended genesis connected to anthropogenic and geogenic measures. Based on calculated water quality index (WQI) values, groundwater falls under two classes: excellent and good water. WQI values of the study region depict that 85.72% of samples come under the excellent category and 14.28% in the good category. © 2021 Wiley Periodicals LLC